Efektivitas Fungsi Pengawasan Badan Permusyawaratan Desa Berdasarkan Peraturan Daerah Kabupaten Lampung Selatan Nomor 2 Tahun 2023 (Studi di Desa Kerawang Sari Kecamatan Natar) - Muhamad Andra Wahyudi; Lintje Ana Marpaung; Okta Ainita (SANGAJI: Jurnal Pemikiran Syariah dan Hukum, 2025)
This study examines the role of the Village Consultative Body (BPD) in carrying out its supervisory function based on South Lampung Regency Regulation No. 2 of 2023 concerning Village Government, with a case study in Kerawang Sari Village, Natar District. The main problem in this study is the suboptimal involvement of the BPD in supervising village administration and the existence of various structural and operational obstacles that hamper the performance of this institution. The purpose of this study is to analyze the effectiveness of the BPD's role in supervision and to identify the obstacles faced in the implementation of the Perda. The research method used is a juridical-empirical approach. Primary data was obtained through observation and interviews with the Village Head and the Chair of the Kerawang Sari Village Council, while secondary data was obtained through a literature study of relevant regulations. Data analysis was conducted qualitatively with deductive conclusions. The results of the study show that the role of the Kerawang Sari Village Council in its supervisory function has not been maximized in accordance with the mandate of Local Regulation No. 2 of 2023. The main obstacles identified include low quality human resources, minimal understanding of regulations, and less than harmonious working relationships with village heads. The conclusion of this study emphasizes the need to improve human resource capacity through ongoing training and strengthened coordination between the BPD and village government.